Incursion of Helminthosporium leaf blight disease of wheat in comparatively cool hilly regions of Nepal - Bhandari, Deepak (Journal of Medical Biomedical and Applied Sciences, 2017)
Helminthosporium Leaf Blight (HLB) caused by Bipolaris sorokiniana (Shoem.) and Pyrenophora tritici repentis (Died.) is the most problematic leaf spotting disease of wheat in warm plain regions of Nepal. Because of increasing temperature, erratic rainfall and changing weather conditions, the disease can also become devastating in vast mid-hill regions having comparatively cool temperature. Various levels of severity and intensity of HLB disease of wheat have been reported from different plain areas of Nepal; however, the confirm status of HLB disease of wheat in mid-hills and hills of Nepal is still lacking. Therefore, a study was carried out to identify the severity and intensity of HLB disease of wheat in five districts of mid-hill during 2012 and 2013 crop season.  Field monitorings were carried out and diseased samples were collected twice at Lalitpur, Bhaktapur, Dhading, Kathmandu and Nuwakot districts during the two crop seasons. The status of wheat crop and associated diseases under field conditions were observed and recorded. About 100 diseased leaf samples were collected from different fields of each site. The samples were than incubated under moist chambers for seven days at room temperature in laboratory of Plant Pathology Division, Lalitpur. After the incubation, the samples were studied under stereoscope microscope for the presence of leaf spotting pathogens. The condition of wheat crop at field was fair to good, and the leaf spotting disease symptoms were very low in most of the visited sites during first monitoring. The growth of the crop was still fair to good; however, considerable symptoms of leaf spotting diseases were observed in penultimate leaf and lower leaves in second monitoring. After heading stage, most of the wheat plants were infected with leaf spotting diseases; nevertheless, only scattered leaf spots were observed in single leaf and the total infected area in each leaf was petite. The intensity of leaf spotting disease was mild in popular wheat variety WK 1204. There was extensive growth of leaf spotting pathogens Bipolaris sorokiniana and Alternaria species on incubated leaf samples. More than 85% leaf samples were infected with devastating pathogen Bipolaris sorokiniana followed by Alternaria spp. and Epicoccum sp. The presence of Pyrenophora tritici repentis was also noticeable. The results indicate that the leaf blight disease of wheat has been increased in areas having moderate temperature, and will be a problem in future for wheat growers of Kathmandu valley and similar mid-hills regions of Nepal.